Statisztikai jelentés a gyermekegészség állapotáról Magyarországon a 21. század második évtizedében - Tamás Hajdu; Gábor Kertesi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
– This report examines health inequalities among Hungarian children in the 2010s. Our work is based on a wide range of administrative and survey data drawn from numerous sources. We analyze the datasets in a unified framework and present the findings in an easily understandable way, by which our report can be informative for not only the academic but the non-academic readers too. We show that children's health is closely related to their social background, income position, living conditions, and the health behaviors of themselves and their parents.
Keywords: I10; I14; J13; 330; health; inequality; children; Hungary